Black and White Body Mass Index Values in Developing 19th Century Nebraska - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2013)
Little is known about late 19th and early 20th century BMIs on the US Central Plains. Using data from the Nebraska state prison, this study demonstrates that the BMIs of dark complexioned blacks were greater than for fairer complexioned mulattos and whites. Although modern BMIs have increased, late 19th and early 20th century BMIs in Nebraska were in normal ranges; neither underweight nor obese individuals were common. Farmer BMIs were consistently greater than non-farmers, and farm laborer BMIs were greater than common laborers. The BMIs of individuals born in Plains states were greater than for other nativities, indicating that rural lifestyles were associated with better net current biological living conditions.
Keywords: I10; J11; J71; N31; 330; 19th century Nebraska; industrialization; BMIs